EMBR-08. CHOROID PLEXUS TUMORS IN 2018: THE CPT-SIOP EXPERIENCE AND LONG-TERM OUTCOME. Issue 2 (22nd June 2018) - Kordes, Uwe R; Hartung, Stefan; Löbel, Ulrike; Ozga, Ann-Kathrin; Traunecker, Heidi; Adamski, Jenny; Filipek, Iwona; Garami, Miklos; Solanki, Guirish; Hasselblatt, Martin; Pietsch, Torsten; Kortmann, Rolf-Dieter; et al.
Abstract: Choroid plexus tumors (CPT) comprise choroid plexus papilloma (CPP, WHO grade I), atypical choroid plexus papilloma (aCPP, WHO grade II), and choroid plexus carcinoma (CPC, WHO grade III). CPT from 20 nations were prospectively recruited into the CPT-SIOP-2000 study (01/2000–03/2010, n=129, median follow-up 7.4 years) and the CPT-SIOP registry (04/2010-01/2018, n=119). Non-surgical risk-stratified treatment consisted of i) chemotherapy for all CPC, all metastatic CPT and incompletely resected aCPP regardless of metastases ii) focal radiotherapy in non-metastatic CPC >3y, iii) craniospinal radiotherapy in non-metastatic CPC >3y during the registry phase. Non-metastatic CPP and aCPP R0 were followed by surveillance. CPT-SIOP-2000 randomized six cycles of carboplatin/VP16/VCR vs. cyclophosphamide/VP16/VCR. Alternating combination of these cycles were given to registry patients with CPC (n=16). WHO grading was the most significant prognostic variable for OS and EFS in CPT patients, five-year OS/EFS accounting for 100/96% in CPP (n=84), 97/79% in aCPP (n=88) and 58/35% in CPC (n=76). Of note, 5y OS/EFS was 100/92% for aCPP patients <2y (n=59) as compared to 85/39% for aCPP patients >2y (n=22). CPCs opting for postop surveillance only progressed with dissemination. Carboplatin based chemotherapy trended superiorly. Clinical staging had minor impact on survival in the primary treatment groups. Radiotherapy for CPC without Li-Fraumeni syndrome had a survival advantage in the first five years of follow-up, craniospinal field did not improve survival for non-metastatic CPC. Delayed radiotherapy for young patients with CPC that progressed on chemotherapy achieved meaningful responses (n=8). In conclusion: adjuvant therapy improves outcome for high risk CPT.